2016
DOI: 10.1136/bmjopen-2015-010155
|View full text |Cite|
|
Sign up to set email alerts
|

Social inequalities in prevalence of diagnosed and undiagnosed diabetes and impaired glucose regulation in participants in the Health Surveys for England series

Abstract: ObjectivesTo ascertain the extent of socioeconomic and health condition inequalities in people with diagnosed and undiagnosed diabetes and impaired glucose regulation (IGR) in random samples of the general population in England, as earlier diagnosis of diabetes and treatment of people with IGR can reduce adverse sequelae of diabetes. Various screening instruments were compared to identify IGR, in addition to undiagnosed diabetes.Design5, annual cross-sectional health examination surveys; data adjusted for comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
84
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 43 publications
18
84
1
2
Order By: Relevance
“…Although the prevalence of 9.2% is lower compared to some Southeast Asian countries; 11.1% in Tamil Nadu (Subramani, Devi, & Shankar, 2014) and 11.1% in Singapore (Huang et al, 2015) but it is nonetheless significantly higher compared to other countries like Canada (2.2%) (Flores-Le Roux et al, 2011) and the United Kingdom (2.0%) (Moody, Cowley, Ng Fat, & Mindell, 2016). These undiagnosed DM in Malaysia could be due to lack of awareness of the necessity of health screening at an earlier age and of early diabetes symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…Although the prevalence of 9.2% is lower compared to some Southeast Asian countries; 11.1% in Tamil Nadu (Subramani, Devi, & Shankar, 2014) and 11.1% in Singapore (Huang et al, 2015) but it is nonetheless significantly higher compared to other countries like Canada (2.2%) (Flores-Le Roux et al, 2011) and the United Kingdom (2.0%) (Moody, Cowley, Ng Fat, & Mindell, 2016). These undiagnosed DM in Malaysia could be due to lack of awareness of the necessity of health screening at an earlier age and of early diabetes symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…Based on existing literature and care guidelines, index HbA 1c , age, and ethnicity/race were included as fixed effects in these models [1921]. …”
Section: Methodsmentioning
confidence: 99%
“…That it can remain asymptomatic for several years contributes to this burden by allowing complications associated with it to accumulate that could be avoided were it detected and managed earlier [8,10,34]. While prompt identification and effective management are clearly important to avoiding such costs, several studies highlight not only the existence of a substantial prevalence of undiagnosed disease [4,14,17,20,28,32] but also the existence of distinct patterns of undiagnosed disease. In the UK, Moody et al [20], for example, found that males, those who are older (greater than 34 years) and those who are ethnic Asians were more likely to have undiagnosed diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…While prompt identification and effective management are clearly important to avoiding such costs, several studies highlight not only the existence of a substantial prevalence of undiagnosed disease [4,14,17,20,28,32] but also the existence of distinct patterns of undiagnosed disease. In the UK, Moody et al [20], for example, found that males, those who are older (greater than 34 years) and those who are ethnic Asians were more likely to have undiagnosed diabetes. In the US, Menke et al (2015) [17] similarly found that rates of undiagnosed diabetes were higher among those who were older (45 years plus) and among Asians compared with Whites or younger persons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation